2009
DOI: 10.1080/10717540903075644
|View full text |Cite
|
Sign up to set email alerts
|

In vivo lymphatic targeting of methylene blue with microemulsion and multiple microemulsion

Abstract: (2009) In vivo lymphatic targeting of methylene blue with microemulsion and multiple microemulsion, Drug Delivery, 16:7,[371][372][373][374][375][376][377]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It also provides protection against enzymatic hydrolysis (Hu et al, 2011). The selection of suitable surfactant combinations is a critical parameter in order to make thermodynamically stable emulsion (Wang et al, 2009). Establishment of a phase diagram is also necessary for the selection of multiple components in microemulsions (Narang et al, 2007).…”
Section: Microemulsionmentioning
confidence: 99%
“…It also provides protection against enzymatic hydrolysis (Hu et al, 2011). The selection of suitable surfactant combinations is a critical parameter in order to make thermodynamically stable emulsion (Wang et al, 2009). Establishment of a phase diagram is also necessary for the selection of multiple components in microemulsions (Narang et al, 2007).…”
Section: Microemulsionmentioning
confidence: 99%
“…Although there are different methods for quantifying MB and MET in their isolated form or associated with other substances (Chengalva, Angala Parameswari, & Aruna, 2016;Chengnan et al, 2019;Chhetri, Thapa, & Van Schepdael, 2014;Khdair, Handa, Mao, & Panyam, 2009;Prasanna & Priyanka, 2015;Rengelshausen et al, 2004;Rostamkalaei, Akbari, Saeedi, Morteza-Semnani, & Nokhodchi, 2019;Umapathi, Ayyappan, & Darlin Quine, 2012;Wang et al, 2009), few studies quantify these substances in a matrix as complex as the skin (Chen et al, 2020;Garcia et al, 2018;Junqueira et al, 2016;Polonini et al, 2019;Yu et al, 2018Yu et al, , 2019 and some of them employ quantitative methods that are not selective (Garcia et al, 2018;Junqueira et al, 2016) or standardized for other matrices such as plasma and urine, which may not be suitable for quantification in the different layers of the skin (Yu et al, 2018(Yu et al, , 2019; moreover, there are no studies in the literature that quantify the two substances simultaneously and in the different layers of the skin (SC and viable epidermis + dermis, VE + D).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, MB-S could only maintain the bluestained state in LNs for a short period. For MB-ME, with the viscosity of 102.75 mPa S (Wang et al, 2009), it exhibited a poor fluidity, leading to a slow removal in lymph. Thus, T max , C max and AUC (0-12h) value of MB-ME in LNs were smaller than other formulations.…”
Section: Lymphatic Uptake and Retentionmentioning
confidence: 99%
“…MB-ME and MB-MME prepared in our previous study (Wang et al, 2009) demonstrated that microemulsion could enhance lymphatic uptake and drainage. However, due to the insoluble property of AB in majority of the solvents, it is difficult to construct nanoparticulate with high drug payload.…”
Section: Study On Drug Concentration In Plasmamentioning
confidence: 99%
See 1 more Smart Citation